Jumping for justice - part 2: Individual jump technique - Haw, D. (The Professional Skater PS Magazine, 2020)
In the March/April issue of PS Magazine, Doug wrote about his systematic approach to jumping with the fixed plan and fail-proof method he uses. In the article, he reviewed his 21 "Jumpisms" that he uses to get a quick fix for jumps. Here he is providing specific tips and exercises to help with each individual jump, starting with the waltz jump. Jump combinations will be addressed in a future article.